Effectiveness of HPV vaccination in reducing infection among young Brazilian women - Ana Carolina da Silva Santos; Nayara Nascimento Toledo Silva; Ismael Dale Cotrim Guerreiro da Silva; Mariângela Carneiro; Wendel Coura-Vital; Angélica Alves Lima (BMC Infectious Diseases)
Abstract Background Globally, cervical cancer is an increasing public health issue, and vaccination against HPV has proven to be an effective strategy to reduce this neoplasia. The purpose of this study was to assess the effectiveness of the quadrivalent vaccine in reducing the prevalence and incidence of HPV infection in women, aged 18 to 24 years old, in the cities of Ouro Preto and Mariana, Minas Gerais, Brazil. Methods A concurrent cohort study was performed, with an initial follow-up of 12 to 18 months. The selected young women were interviewed and divided into two groups: vaccinated and unvaccinated. Participants underwent a Pap smear and cervical sample collection for HPV detection, genotyping performed by PCR-RFLP, type-specific PCR, and using the PapilloCheck®. The prevalence of HPV infection was analyzed using the compare proportions test. Poisson and Cox multivariate regression models were used to estimate vaccine effectiveness. Results There was no significant difference in the overall prevalence of HPV infection between vaccinated and unvaccinated groups (23.6% vs. 18.7%; p = 0.364). However, the prevalence of infection by HPV 6/11, 16 and 18 types in vaccinated young women (1.1%) was lower than in unvaccinated ones (7.5%; p = 0.030). Regarding non-vaccine types, a higher prevalence was identified among vaccinated women (22.5% vs. 11.2%; p = 0.018). The overall incidence of HPV infection was 15.75/100 young women/year in non-immunized women compared to 9.12/100 young women/year among those immunized. The effectiveness of the vaccine was 64.0%, regardless of the viral type, and no vaccinated woman was detected with the specific vaccine HPV-type in follow-up. HPV33/45, related to cross-protection, were detected in 12.3% of vaccinated women and 1.2% of unvaccinated ones (p < 0.001) at baseline. These viral types were identified at follow-up in 2.03/100 young women/year of vaccinated participants and 4.24/100 young women/year of unvaccinated ones. Conclusions The results showed that the quadrivalent HPV vaccine was effective in reducing the prevalence of vaccine-type HPV and the incidence of infection by any HPV type. Public health policies must encourage vaccination to prevent HPV infection. However, surveillance of HPV infection should be continued to assess the prevalence of different genotypes and the impact of the vaccination program.